Determinación de la contaminación orgánica por el índice de saprobidad en el estero Huaylá - Espinosa Nieto, Ronald Eugenio (2012)
This thesis was carried out to determine the level of organic pollution in the estuary and set Huayla saprobidad index. It was along the estuary, taking three points, the beginning of the stream that begins in the district on November 8, the middle of the stream that falls short of the Yacht Club and the output stream that is where it empties into a larger one as Santa Rosa. Huayla estuary pollution is mainly due to the discharge of raw sewage from the city of Machala, which impair its waters adjacent to the marsh people throw all kinds of domestic, industrial, plastic, glass, oil residues , disinfectants and large amounts of domestic waste water discharges loaded with fecal matter, it is used as a transport route for the artisanal fishing fleet, dock work, and the shrimp they use as fuel to diesel and bunker for their boats. Water samples monitored at different sampling points were processed "in situ" with 2% formalin trasladas amber jars for samples of phytoplankton and zooplankton parameters were determined in parallel with dissolved oxygen, pH, turbidity, salinity and temperature to determine the other variables were used bottles of 1000 ml amber and taken to laboratories laboratories of the Faculty of Agricultural Sciences. After making the corresponding analysis and compare the results with the rate of contamination found in the table Saprobidad level concerning the biochemical oxygen demand indicates that the level is Contaminated in the three sampling points of the estuary Huayla when Quadratura is the ebb and flow. In the three sampling points of the estuary organic pollution is very high in Quadratura when in high and low tide. The average level in the inlet Huayla saprobidad is Polisaprobidad, especially where the starting point is 10. With an average frequency of occurrence of all species of 2.8. Through experimentation in the estuary Huayla of the three sampling points analysis determined that all are above the upper limit of 6 withwhat is described as very high. If we analyze average, the three points is 7.6 which is still high. For analysis of the estuary saprobidadHuayla, taking as bio indicator to plankton, the analysis determined that all sampling points has a level of polisaprobidad, corroboratedwith the analysis of biochemical oxygen demand, is to take into consideration that the point start being the most polluted throw of 10.7. You could say that is larger because in this place is dumped as much water served Machala canton.